THE TYPE OF CHRIST IN PASSOVER - Warouw, Winda Novita (Klabat Theological Review, 2021)
Two explanations that are referring to biblical typology in this research are its terminology and its meaning. The term typology comes from the Greek typos, meaning “copy, picture, pattern.” Typology generally contains two elements: type, the initial element, and antitype, the other element. Typology, in particular, can be placed in the form of a relationship between the OT and NT. Accordingly, a “type” is an event, person, or object, meaning prefigures or foreshadows any subsequent event, subject, or object, while “antitype” is the fulfilment or manifestation of those types. The Passover was the first of the three annual festivals in which all the people of Israel will come before God and with it is the Feast of Unleavened Bread. The earliest evidence for the use of Passover wine comes from the Hellenistic period. The Passover feast was celebrated with four cups of wine to uphold the Jewish tradition, symbolizing the four redemption signs found in (Exo 6:6). Through the study of the biblical record, it is assumed that: (1) Jesus Christ is indeed the antitype of the types found in the Passover festival; (2) Jesus is the manifestation of the Passover through the bread, wine, and lamb; and (3) There is a couple of practical implications found in this research: (a) because the Passover bread symbolizes the body of Jesus, there is a clearer picture that Jesus is the true savior for he was sinless (unleavened) when he lived on earth; (b) just as the wine represents the blood of Jesus, and blood refers to life itself, it is evident that only through Jesus, mankind may have eternal life; and (c) the fact that Jesus is the antitype of the Passover lamb indicates that only through him that the victory over sin can be truly reached. Keywords: Type, Passover